Citizen Journalism and Public Participation in the Era of New Media in Indonesia: From Street to Tweet - Syahputra, Iswandi (2019)
Citizen journalism was initially practiced via mass media. This is because citizens trusted mass media as an independent information channel, and social media like Twitter was unavailable. Following mass media’s affiliation to political parties and the rise of social media, citizens began using Twitter for delivering news or information. We dub this as citizen journalism from street to tweet. This study found that such process indicates the waning of mass media and the intensification of social media. Yet, the process neither strengthened citizen journalism nor increased public participation as it resulted in netizens experiencing severe polarization between groups critical and in support of the government instead. We consider this as a new emerging phenomenon caused by the advent of new media in the post-truth era. In this context, post-truth refers to social and political conditions wherein citizens no longer respect the truth due to political polarization, fake-news-producing journalist, hate-mongering citizen journalism, and unregulated social media activities. Primary data were obtained through in-depth interviews with four informants. While conversation data of netizens on Twitter were acquired from a Twitter conversation reader operated by DEA (Drone Emprit Academic), a big data system capable of capturing and analyzing netizen’s conversations, particularly on Twitter in real time. This study may have implications on the shift of citizen journalism due to its presence in the era of new media. The most salient feature in this new period is the obscurity of news, information, and opinions conveyed by citizens via social media, like Twitter.